EFEKTIFITAS JUS BELIMBING WULUH TERHADAP PENURUNAN KADAR KOLESTEROL PADA LANSIA DI PUSKESMAS DUNGALIYO KECAMATAN DUNGALIYO KABUPATEN GORONTALO - Rosmin Ilham; Nur Uyuun I. Biahimo (-, 2021)
One of non pharmacological therapies of its problem is giving star fruit juice. The objective of this research is to find out Affectivity of Star fruit Juice on Decreasing Cholesterol Level on elderly at Puskesmas Dunggaliyo. Design of research used quasi eksperimen with two group pretest posttest only design. The explanation of this research about all the elderly at Puskesmas Dunggaliyo with 66 elderly. The samples used 20 respondents. Analyzing data used paired T Test statistical test. The result showed there are the average of cholesterol level of elderly at Puskesmas Dunggaliyo before giving star fruits juice 219,5% gr/dl, average of cholesterol after giving star fruits juice 197,1 gr/dl. The conclusion is the star fruits juice effectively could decrease cholesterol level in elderly (p value 0,000). Recommendation for this research result could be considered to use as one of intervention of the nurses to elderly who has high level of blood cholesterol.